1983
DOI: 10.3758/bf03199777
|View full text |Cite
|
Sign up to set email alerts
|

Herrnstein’s equation for the rates of responding during concurrent schedules

Abstract: A modification of the nonlinear curve-fitting procedure proposed by Wetherington and Lucas (1980) was used to assess how well Herrnstein's (1970) equation for the rates of responding during concurrent schedules described performance. The equation fitted some results very well, accounting for 80% or more of the variance in the data in studies that used moderateduration changeover delays and provided the same positive reinforcers, operanda, and simple schedules in the two components. The equation fitted the data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 56 publications
0
18
1
Order By: Relevance
“…For example, a reanalysis of de Villiers and Herrnstein (1976) indicated that only 78% of the variance was accounted for when these averaging procedures were eliminated, as opposed to the 94% originally reported by those authors. In addition, McSweeney et al (1983) found very low percentages of variance accounted for in a number of situations when single-subject data were analyzed. The present values, therefore, may be well within the normal range.…”
Section: Discussionmentioning
confidence: 95%
“…For example, a reanalysis of de Villiers and Herrnstein (1976) indicated that only 78% of the variance was accounted for when these averaging procedures were eliminated, as opposed to the 94% originally reported by those authors. In addition, McSweeney et al (1983) found very low percentages of variance accounted for in a number of situations when single-subject data were analyzed. The present values, therefore, may be well within the normal range.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, taking undermatching and bias into account in Equation 5 yielded estimates of R~that were positive, were in a plausible range (cf. McSweeney et al, 1983), and were systematically related to the obtained RL values. That is, the Rṽ alues estimated by taking undermatching and bias into account were consistent with Herrnstein's interpretation.…”
Section: R-----omentioning
confidence: 99%
“…Finally, derivation of the matching law requires that a number of assumptions be made concerning the control of behavior (Timberlake, 1982). Recently, several authors have questioned the validity of these assumptions (Dougan & McSweeney, 1985;McSweeney, Melville, & Whipple, 1983;Timberlake, 1982). As Timberlake has argued, the matching law cannot be considered a general theory of behavior unless the assumptions of matching can be supported.…”
Section: Subjectsmentioning
confidence: 99%